2017
DOI: 10.1159/000471854
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Induce Stemness in the Stromal Cells of a CT26 Mouse Tumor Model

Abstract: The potential effects of 2 types of fatty acids on colorectal cancer (CRC) were assessed using cancer stromal cells. Linoleic acid (LA; C-18, n-6 unsaturated fatty acid) and elaidic acid (EA; C-18, trans acid), both known to affect colon carcinogenesis and cancer progression, were administered by gavage to BALB/c mice, which were inoculated with CT26 syngeneic colon cancer cells in the back. Both EA and LA treatments enhanced tumor growth and metastasis. EA and LA also increased the number of CD133-positive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Lipid unsaturation is essential in breast, colon, and prostate cancer cells [ 105 , 106 ]. Administration of unsaturated fatty acids by gavage to BALB/c mice pre-inoculated with colorectal cancer cells amplify CD133(+) subpopulations, induces stemness and promotes tumor formation and metastasis [ 107 ]. Most mono-unsaturated fatty acids (MUFAs) are the catalytic product of stearoyl-CoA desaturase (SCD) (Fig.…”
Section: Alterations In Lipid Metabolism In Cscsmentioning
confidence: 99%
“…Lipid unsaturation is essential in breast, colon, and prostate cancer cells [ 105 , 106 ]. Administration of unsaturated fatty acids by gavage to BALB/c mice pre-inoculated with colorectal cancer cells amplify CD133(+) subpopulations, induces stemness and promotes tumor formation and metastasis [ 107 ]. Most mono-unsaturated fatty acids (MUFAs) are the catalytic product of stearoyl-CoA desaturase (SCD) (Fig.…”
Section: Alterations In Lipid Metabolism In Cscsmentioning
confidence: 99%
“…Previous studies describe unsaturated fatty acid as a stabilizer of oncogenes that function to promote cell growth and inhibit apoptosis (10)(11)(12)(13)(14). This suggests that the presence of unsaturated lipids in ccRCC is necessary for growth and survival (15)(16)(17)(18)(19)(20)(21). However, there is growing evidence that demonstrates a positive correlation between MUFAs and survival in various model systems (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…CT26 mouse colon cancer cells were inoculated on the backs of BALB/c mice, and LA was administered by gavage. The results showed that LA promoted tumor cell growth and induced cancer cell stemness, which in turn promoted tumor metastasis [ 60 ]. Nude mice transplanted with human gastric cancer cells (OCUM-2MD3) and then fed LA showed that LA could stimulate gastric cancer cell invasion and peritoneal metastasis by cyclooxygenase (COX)-catalyzed metabolism and ERK activation [ 61 ].…”
Section: Fatty Acids In the Diet And Their Relationship To Cancermentioning
confidence: 99%